2006
DOI: 10.1161/01.str.0000204118.87477.46
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Incidence of Retinal Emboli in an Older Population

Abstract: Background and Purpose-To assess 10-year incidence of retinal emboli and its predictors in an older population. Methods-Survivors of 3654 Blue Mountains Eye Study participants Ն49 years of age were re-examined 5 and 10 years later. Incident emboli were assessed from retinal photographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…Other studies have reported a cumulative incidence of 1.5–2.9% over 10 years [8, 9], which is similar to our finding. In the first year of the screening program, the prevalence of retinal emboli in the local area was 1.5% (personal communication with DHW Steel).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have reported a cumulative incidence of 1.5–2.9% over 10 years [8, 9], which is similar to our finding. In the first year of the screening program, the prevalence of retinal emboli in the local area was 1.5% (personal communication with DHW Steel).…”
Section: Discussionsupporting
confidence: 93%
“…The BMES showed that 18% of people with retinal emboli compared to 12% without had non‐diabetic retinopathy lesions but the statistical significance was unreported . The 10 year follow‐up of the BMES cohort showed that AV nicking, arteriolar wall opacification and retinal vein occlusion predict incident retinal embolism . Other microvascular parameters such as focal or general arteriolar narrowing have not shown association with the presence of retinal emboli so far in cross‐sectional or prospective population‐based studies.…”
Section: Retinal Arteriolar Emboli and Occlusionmentioning
confidence: 97%
“…Although less frequently reported than the other retinal vascular disease states, there is no evidence of associations between retinal microvascular changes and prevalent or incident retinal embolism (Table ). This is with the exception of the BDES where at the 5 year analysis, the presence of retinopathy in non‐diabetic subjects had a fourfold higher risk of prevalent embolism; however, no measures were associated with incident emboli at either the 5 or 10 year analysis .…”
Section: Retinal Arteriolar Emboli and Occlusionmentioning
confidence: 99%
“…Risk factors for the development of CRAO are similar to those of other cardiovascular diseases, namely increasing age, hypertension, hypercholesterolemia, diabetes, elevated homocysteine levels, and tobacco use. Some studies have described an increased incidence in males, whereas others have failed to demonstrate a difference in disease prevalence in one sex over the other [46][47][48].…”
Section: Epidemiologymentioning
confidence: 99%